Vascular reactivity and biomarkers of endothelial function in healthy subjects exposed to acute hypobaric hypoxia - Iglesias, Diego (2015)
Aims: The aim of this study was to evaluate the effects of acute hypobaric hypoxia (HH) on vascular reactivity and biochemical markers associated with endothelial function (EF). Main methods: Ten healthy subjects were exposed to a simulated altitude of 4,000. meters above sea level for 4. hours in a hypobaric chamber. Vascular reactivity was measured by the flow-mediated vasodilatation (FMVD) test. Endothelin-1, high sensitive-C reactive protein (hsCRP), vascular cell adhesion molecule 1, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), paraoxonase and adiponectin levels, and FMVD were evaluated before and after the exposure. Key findings: Subjects were young (age: 32±6years), lean [body mass index: 23.9±2.0kg/m2, waist circumference: 77(IQR: 72-80) cm], and presented normal clinical and biochemical parameters. No significant changes were evidenced in FMVD in response to HH (pre: 0.45 (0.20-0.70) vs. during: 0.50 (0.20-1.22) mm; p=0.594). On the other hand, endothelin-1 (+54%, p<0.05), hsCRP (+37%, p<0.001), IL-6 (+75%, p<0.05), TNF-α (+75%, p<0.05), and adiponectin (-39%, p<0.01) levels were significantly altered post-HH. FMVD was increased in 7 subjects, and it was decreased in 3 individuals during HH exposure. Interestingly, when EF biomarkers were compared between these two subgroups of subjects, only post exposure-adiponectin levels were significantly different (49±5 vs. 38±6μg/ml, respectively, p<0.05). Significance: HH exposure had an effect on endothelin-1, adiponectin, hsCRP, IL-6, and TNF-α concentration. However, adiponectin was the only biomarker associated with an altered vascular reactivity.